(untitled) (Research, Society and Development, 2023)
Access to oral health is a problem faced by many countries in the world as well as Brazil. The objective was to analyze the relationship between access to public dental services in Primary Health Care with individual and contextual factors. Cross-sectional study with a sample of adult subjects of both sexes, carried out in the city of São Paulo/SP from 2022 to 2023. The dependent variable was access, categorized into: scheduled access and unscheduled access. Descriptive analyzes were performed and later binary logistic regression models were estimated, with 95% CI and p<0.05. 109 subjects participated in the study, 74.3% female, age group ranged from 18 to 79 years old. Being of black race/color means having 5.42 times more chance of accessing the service through unscheduled access mode; as pardo has 5.01 times more chance; treatment/pain, means having 3.55 times more chances of accessing the service through unscheduled access; as well as nervous/irritated with your teeth, means having 3.18 times more chance. Access can be qualified for greater equity in dental services, as it is influenced by individual and demographic dental factors.